Bio-efficacy of pumpkin phloem lectin on red spider mite, Oligonychus coffeae (Nietner) infesting tea - Kalaivani, A.; Sathyapriya, P.; Arvinth, S.; Kumar, R. Raj; kumar, P. Mohan (Journal of Plantation Crops, 2019)
----------------